Same‐sex marriage and the public policy process. Issue 1 (27th June 2019) - Cravens, Royal G.
Abstract: How did same‐sex marriage come to be adopted as public policy in the United States? In this expository essay, I draw on multiple streams, social construction, and punctuated equilibrium theories to analyze the changes in policy definition, policy venue, the focusing events, indicators, and feedback which led to the placement of same‐sex marriage on the institutional agenda of the Supreme Court. I conclude that same‐sex marriage represents the policy solution to the problem of Lesbian, Gay, Bisexual, and Transgender (LGBT) inequality which corresponded best with the political environment in the United States at the time of its endorsement by the Supreme Court. By synthesizing the social construction literature and critiques of same‐sex marriage derived from queer theory, however, I highlight the consequences of forgoing policy alternatives in favor of same‐sex marriage for LGBT people who do not fit dominant constructions of sexual minority identity. 摘要: 同性婚姻是如何在美国成为一项公共政策的？在这篇阐述性文章中，笔者运用多源流、社会建构和间断平衡理论，分析了导致同性婚姻纳入最高法院制度议程的一系列政策定义变化、政策舞台、焦点事件、指示物、和反馈。笔者结论认为，同性婚姻代表了LGBT不平等问题的政策解决措施，该措施受到最高法院许可一事正好回应了当时的美国政治环境。通过将社会建构文献和取自酷儿理论的同性婚姻评论进行结合，笔者强调，放弃支持同性婚姻的政策选择，可能会对那些不适应"有关性少数认同的主流建构"的LGBT人群产生后果。 Resumen: ¿Cómo fue implementado como política pública el matrimonio del mismo sexo en los Estados Unidos? En este ensayo expositivo, recurro a múltiples corrientes, construcción social y teorías de equilibrio puntuado para analizar los cambios en la definición de políticas, el lugar de las políticas, los eventos de enfoque, los indicadores y la retroalimentación que llevaron a la colocación del matrimonio del mismo sexo en la agenda institucional de la Corte Suprema. Concluyo que el matrimonio del mismo sexo representa una solución política para el problema de la desigualdad de la población LGBT que corresponde mejor al ambiente político en los Estados Unidos al momento en que fue respaldado por la Corte Suprema. Al sintetizar la literatura de la construcción social y las críticas del matrimonio del mismo sexo derivadas de la teoría queer, sin embargo, resalto las consecuencias de abstenerse de usar las alternativas políticas a favor del matrimonio del mismo sexo para personas LGBT que no encajan en las construcciones dominantes de la identidad de las minorías sexuales.